PERAN KOPERASI SIMPAN PINJAM DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DESA MONDANG SOSA KABUPATEN PADANG LAWAS - Sawaluddin Siregar; Dahliati Simanjuntak; Agustina Damanik (Yayasan Baitul Hikmah al-Zain, 2025)
In economic activities, cooperatives play a role in helping the economic development of the community by carrying out empowerment. Where empowerment is an effort to meet the needs desired by individuals, groups and the wider community so that they have the ability to make choices and control their environment in order to fulfill their desires, including their accessibility to resources related to their work, social activities, and so on. In this journal, there are two problem formulations, namely how are the efforts of savings and loan cooperatives in empowering the community's economy in Mondang Village, Sosa District, Padang Lawas Regency?. What is the level of welfare of the people in Mondang Village, Sosa District, Padang Lawas Regency who are members of the savings and loan cooperative? This type of research is field research, which is a research conducted at the research location by making observations about a phenomenon in a natural state. Meanwhile, data collection in this study uses observation, interview, and documentation methods. This study uses qualitative descriptive analysis and descriptive statistics with a qualitative approach. The location of the research was carried out at KSP Mondang Village, Sosa District, Padang Lawas Regency. The results of this study show that KSP Mondang Village, Sosa District, Padang Lawas Regency has efforts to empower the community in improving welfare. In addition, the level of welfare of the members is quite good with several welfare indicators that have been met.